The Efficacy of Adding Electromagnetic Therapy or Laser Therapy to Medications in Patients With Diabetic Peripheral Neuropathy - Shanb, Alsayed; Youssef, Enas; Al Baker, Waleed; Al-Khamis, Fahd; Jatoi, Noor ahmad; Hassan, Ali (Journal of Lasers in Medical Sciences, 2020)
Introduction: Diabetes mellitus (DM) is a common disease with a highly significant burden among the Saudi population. This study aimed to investigate the effects of adding either magnetic or laser therapy to medications in patients with diabetic peripheral neuropathy (DPN). Methods: Seventy-one medically controlled diabetic patients were randomly assigned to 1) Magnetic group: 26 patients were exposed to magnetic therapy for 20 minutes/session, 2 sessions/week, for 3 months 2) Laser group: 25 patients were exposed to laser therapy with intensity 5.7 J/cm2 for 30 minutes/session, 2 times/week, for 3 months. 3) Drug group: 20 patients received only the regular medications for diabetic control and pain analgesia. Pain and neuropathy were assessed by the visual analog scale (VAS) and the Toronto Clinical Neuropath Scoring System (TRCNSS). Conduction velocities and amplitudes of peroneal and sural nerves were measured by electromyography. Results: The results showed significant increases in conduction velocities and amplitudes in both magnetic and laser groups in parallel with significant reductions in TRCNSS. Non-significant changes were obtained only after using only medications (P > 0.05). The mean values of VAS reduced significantly in the three groups. The least significant differences showed significant changes among the three groups, whereas non-significant differences were obtained between both magnetic and laser groups. Conclusion: There were non-significant differences between both magnetic and laser therapy groups. Addition of either magnetic or laser therapy to medications could bring extra positive benefits to patients with DPN. Both magnetic and laser therapy can be applied with medications for the treatment of patients with DPN.